Teachers' Views on Technology in Teaching English at Senior High School Level in Sidoarjo - Yuli Astutik; Nurul Faiza; Zahra Novianti; Naura Nabzifa; Binar Fajar Ismail; Khoirul Umam; Hartini Diaz Febrian; Pratiwi Samsugiyarni (Universitas Muhammadiyah Sidoarjo, 2024)
The integration of technology in English language teaching has significantly reshaped educational practices at senior high school levels. This study investigates teachers' perspectives on the impact of technology on English learning at SMA Muhammadiyah in Sidoarjo, identifying its benefits and challenges. While technology enhances teaching effectiveness by fostering interactive, engaging, and resource-rich environments, it also poses challenges such as inadequate teacher training and difficulties in managing student focus. This research employs a qualitative methodology, involving semi-structured interviews with three English teachers representing different grade levels. The findings reveal that tools like smartboards and platforms such as Nearpod improve student engagement, lesson flexibility, and administrative efficiency. Teachers also highlighted the role of technology in creative lesson delivery and reducing convensional workloads, enabling a more dynamic and enjoyable learning experience. However, disparities in technology access across classrooms and students' overreliance on gadgets were identified as significant barriers. The study underscores the importance of continuous teacher training and equitable technological infrastructure to maximize its benefits. It also emphasizes the necessity for strategic adaptation in leveraging technology to align with students' needs while addressing classroom management challenges. These insights provide a foundation for advancing the integration of technology into English language teaching, promoting more inclusive and impactful educational practices. Highlights: Interactive Tools: Smartboards and platforms like Nearpod enhance student engagement and lesson flexibility. Teacher Challenges: Inadequate training and managing student focus are key barriers to effective technology use. Equitable Access: Ensuring consistent technological resources across classrooms is vital for inclusivity. Keywords: technology integration; English teaching; teacher perspectives; qualitative research; classroom innovation.